Superconducting coplanar microwave resonators with operating frequencies up to 50 GHz. (5th October 2018) - Rausch, Desirée S; Thiemann, Markus; Dressel, Martin; Bothner, Daniel; Koelle, Dieter; Kleiner, Reinhold; Scheffler, Marc
Abstract: We demonstrate the operation of superconducting coplanar microwave resonators in a very large frequency range up to 50 GHz. The resonators are fabricated from niobium thin films on sapphire substrates and have fundamental frequencies of 5 GHz or 10 GHz. We study numerous harmonics of the resonators at temperatures between 1.5 K and 6 K, and we determine quality factors of up to 22 600 at 1.5 K. As an example for spectroscopy applications of such resonators we detect the superconducting transition of a bulk tin sample at multiple probing frequencies.